A RESISTANCE TEST OF OIL PALM VARIETIES (ELAEIS GUINEENSIS JACQ.) IN THE SALINE SOIL WITH AN ADDUCTION OF HUMIC ACID - Gunawan, Hari; Rosmayati, Rosmayati; Sabrina, T. (Universitas Negeri Medan, 2018)
Abstract The objective of the research was to determine theoil palm variety with saline resistance and identify the effective humic acid application dosage with a different salinity rate. This research was conducted in Percut Village.The method used was Randomized Block Design Factorial with 3 factors applied in to 6 varieties oil palm, humic acid dosage (3 dosages) and salinity rate (3 rate) with 3 replications. The results of this research showed that the salinity rate affected significantly to oil palm morphology in saline soil with humic acid adduction. In S0 (0 mmhos), Yangambi variety can increase oil palm plant height, number of leaves, root volume and dry weight of roots. Keywords : Humic Acid, Oil Palm, Saline, VarietyAbstract The objective of the research was to determine the oil palm variety with saline resistance and identifythe effective humic acid application dosage with a different salinity rate. This research was conductedin Percut Village. The method used was Randomized Block Design Factorial with 3 factors applied into 6 varieties oil palm, humic acid dosage (3 dosages) and salinity rate (3 rate) with 3 replications.The results of this research showed that the salinity rate affected significantly to oil palm morphologyin saline soil with humic acid adduction. In S0 (0 mmhos), Yangambi variety can increase oil palmplant height, number of leaves, root volume and dry weight of roots.Keywords : Humic Acid, Oil Palm, Saline, Variety